(untitled) (INTERNATIONAL SEMINAR, 2025)
Heterogeneous catalysts such as activated carbon, metal–organic frameworks (MOFs), and their composites have been increasingly explored for biodiesel production due to their potential reusability and ease of separation. However, the practical performance of these catalysts in palm-oil transesterification often deviates significantly from theoretical expectations, especially in early-stage laboratory trials. This study provides a descriptive account of the initial experimental attempts using three catalysts—activated carbon (AC), ZIF-67, and an AC/ZIF-67 composite—under controlled transesterification conditions. Although no distinct biodiesel–glycerol phase separation was achieved, valuable insights were obtained regarding catalyst dispersion, reaction stability, and emulsion formation. Several factors contributed to the unsuccessful conversion, including incomplete catalyst activation, limited methanol–oil interaction, strong emulsion formation, and mass-transfer resistance. The observations are discussed in light of known mechanistic behavior of solid catalysts in biodiesel systems. A roadmap for improving catalyst activation, operating parameters, and experimental workflow is proposed to guide future work. This contribution highlights the importance of understanding early-stage experimental challenges, especially when novel porous catalysts are introduced to complex liquid–solid reaction systems.